2015
DOI: 10.1007/s10934-015-0005-y
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a Substituted Imidazolate Material 1 (SIM-1) membrane using post synthetic modification (PSM) for pervaporation of water/ethanol mixtures

Abstract: Post synthetic modification (PSM) of metal organic frameworks (MOFs) is a useful tactic used amongst researchers to refine a MOF's properties for an application of interest. In this report, we post synthetically modified a MOF known as Substituted Imidazolate Material 1 (SIM-1) to refine its molecular sieving potential. PSM of ethylenediamine, EDA, vapor was applied to a SIM-1 wafer. EDA cross-linked MOF crystals together through a Schiff base condensation reaction with SIM-1's reactive aldehyde linker forming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 51 publications
(56 reference statements)
0
11
0
Order By: Relevance
“…An alternative approach, termed postsynthetic polymerization (PSP), uses a reactive handle on the MOF that can combine with monomers to form an interstitial polymer matrix around the MOF particles. PSP has been successfully used to prepare membranes and stable, highly connected monoliths …”
Section: Methodsmentioning
confidence: 99%
“…An alternative approach, termed postsynthetic polymerization (PSP), uses a reactive handle on the MOF that can combine with monomers to form an interstitial polymer matrix around the MOF particles. PSP has been successfully used to prepare membranes and stable, highly connected monoliths …”
Section: Methodsmentioning
confidence: 99%
“…ZIF-94/SIM-1 has already been used as membrane material in some publications. Marti et al [40] reported the fabrication of SIM-1 membranes by post synthetic modification of ZIF 8 particles for the separation of water from water/ethanol mixtures. The membrane fabricated using nano SIM-1 crystals separated water completely from the mixture.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by this strategy, some high performance MOFs membranes by post-synthetic modification such as post-modified SIM-1 membrane for pervaporation and post-functionalized ZIF-90 membrane for H 2 separation have been reported [34,35] . Xin et al .…”
Section: Introductionmentioning
confidence: 99%